ANALISA SISTEM PEMBANGKIT THERMOELEKTRIK DENGAN RANGKAIAN PARAREL PADA PEMANFAATAN PANAS BUANG MESIN TOYOTA COROLLA EFI - Agus Wibowo; Zulfah .; Prawiro Anggianto (Engineering : Jurnal Bidang Teknik, 2011)
In the coming year is estimated to be growing energy needs increased by about 40% ofcurrent needs,  as  we know  from  100% fuel  used by  only  about 30% that  is used  to  drive thecar. part of the energy wasted in the form of the radiator and the gas is wasted purpose ofThis  analysis  is  to determine  how to  utilize  waste  heat  energy  in  toyota  corolla  engineefficiently  into  energy  useful  to the  system  and  to determine the  effect  thermolektrik  parallel circuit  thermoelektrik  components  generated  strong  currents  and  voltages  generatedelectricity in accordance with the type of materials used.In  writing  this essay  the author  collected  data  -  data  with  methods of  literature, interviews and observation.There results can be conclude (1) for exhausted heat energy in Corrola EFI Toyota engines are asw follows. Arranging thermoelektrik with parallel circuit which is mounted on the exhaust side, turn the machine with 1000 rpm engine speed, gradually up to 300 0 rpm. Start measuring the temperature of top and bottom of these thermoelektrik, and also a strong measure of current, voltage to be produced thermoelektrik. There we received the results from the engine exhaust heat is on with a series of parallel thermoelektrik. (2) there researchon the  influence of  these  parallel  series  of  studies  thermoelektrik  components  that  wereassembled  in  parallel  to  produce  strong  currents  and tension  resulting  from the  wasteexhaust  heat  is wasted.  at  1000  rpm  to produce  strong  currents  of  0.5  degrees  Celsiusampere  and  voltage  of  0.9  volt  temperature  -  average  above  45  degrees  Celsius,  the temperature  -  average  95  degrees  Celsius  below  1500  rpm  to produce  strong  currents  of  0.9ampere and voltage of 1 volt and temperature - average 59 degrees Celsius.temperature  -  average  below  111  degrees  Celsius.  2000  rpm  producing  a strong  current  of  1ampere  and  voltage  of  1.2  volts  and  temperatures  average  61  degrees  Celsius,  the temperature  -  average  below  119  degrees  Celsius,  2500  rpm  producing  a strong  current  of1.5  amperes  and the  voltage  at  1,  5  volts  and  temperature  -  average  56  degrees  Celsius,  the temperature – average below 123 degree Celsius. 3000 rpm to produce strong currents of 1.5amperes  and the  voltage  of  2  volts  and  temperature  -  average  61  degrees  Celsius,  the temperature  -  average  below  127  degrees  Celsius.  if  understood  parallel  pengaruhrangkaianis still very small to generate strong currents and voltages. the stronger the currents used, the greater the stronger the smaller the current and voltage and vice versa.Key words : ampere, temperature, voltase, thermoelektrik